The Urgency of Social Studies Education in The Globalization Era - Dyah Setyarini (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
This article describes the impact of globalization on the world of education and the urgency of social studies education in facing globalization. Globalization, which brings in foreign cultures through technology, society, and others, can add to the repertoire of cultural diversity within the nation, but on the other hand, globalization can become a dangerous threat in every aspect of our nation's life. Facing this phenomenon, social studies education should ideally be responsive and self-organizing in dealing with globalization. Materials repeated from the start to fail in practice are made into basic materials to work with students to strengthen the spirit of nationalism in the era of globalization.